Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Karakter Peserta Didik di MI Al Falah I Kadur Pamekasan - Kholik, Abd (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Islamic Religious Education teachers play a significant role in instilling character values in their students. They hold a strategic position as the primary actors. A teacher's attitude and behavior leave a lasting impression on students, reflecting their character and personality. Teachers have a significant responsibility in producing a generation with character, culture, and morals. Many students are unable to apply character values in the school or home environment. This research is a field research study, requiring researchers to go into the field to observe a phenomenon in a natural setting. The data sources used are primary and secondary data sources. The results show that the role of Islamic Religious Education teachers in instilling character values in students can be achieved through group activities, with the hope of instilling discipline and responsibility. In addition, the implementation of the 7s (smile, greeting, courteous, polite, patient, and grateful) is also supported. Methods used in instilling character values include role models, advice, demonstrations, and discussions. Supporting factors in instilling character values include the availability of supporting facilities and infrastructure and storytelling media. Meanwhile, inhibiting factors in instilling character values include parents' busy schedules, the environment, and the mass media. Furthermore, solutions to overcome obstacles to instilling character values include giving assignments and collaboration between teachers and parents.